3D flow in a peripheral fan. (4th August 2014) - Weise, Volkmar; Beilke, Jorn
In this work steady–state and transient calculations of the 3D flow in a peripheral fan are presented and compared to theoretically predicted and experimentally observed results. In contrast to axial or radial fans the internal flow in peripheral fans cannot be treated assuming rotational symmetric. The pressure rise in circumferential direction requires the whole time varying geometry, including inlet and outlet, to be taken into account. The numerical results were validated by steady–state measurements of flow velocity components with hot–wire anemometry and transient pressure measurements near the stripper. These results show a good qualitative agreement with the numerically estimated flow characteristics.